Analysis of Students’ Comprehension and Misconception towards the Topic of Salt Solubility - Izzati, Sabila; Rochmah, Nur (Department of Science Education, Universitas Sultan Ageng Tirtayasa, 2020)
This study aimed to analyze students’ comprehension and misconception towards the topic of salt solubility both on the level of microscopic representation and understanding. This study utilized essay diagnostic test as instruments and interviews based on a case study of 10 students in grade 11 at senior high school in Bogor who were given 8 questions regarding salt solubility. The results showed that there was a misconception, 40% of the students misled in drawing microscopically the system of salt and sugar solubility and 50% of the students incorrectly drew the system due to the absence of interaction between salt particle and water, while 10% of the students sketched correctly though it is difficult to notice the result of salt ionization on the solvent. Moreover, 80% of the students were unable to find a link between the alteration system of solvent equilibrium caused by additional salt with various solvents on the macroscopic concept of an insoluble salt equilibrium system and the effect of adding similar ions on the equilibrium system.